2021
DOI: 10.3390/jcm10173799
|View full text |Cite
|
Sign up to set email alerts
|

Topo-Pachimetric Accelerated Epi-On Cross-Linking Compared to the Dresden Protocol Using Riboflavin with Vitamin E TPGS: Results of a 2-Year Randomized Study

Abstract: In the present study (clinical trial registration number: NCT05019768), we compared the clinical outcome of corneal cross-linking with either the standard Dresden (sCXL) or the accelerated custom-fast (aCFXL) ultraviolet A irradiation protocol using riboflavin–D-α-tocopheryl poly(ethylene glycol)-1000 succinate for progressive keratoconus. Fifty-four eyes of forty-one patients were randomized to either of the two CXL protocols and checked before treatment and at the 2-year follow-up. The sCXL group was subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a recent study, corneal cross-linking for progressive keratoconus was compared to ultraviolet A irradiation using the conventional Dresden or accelerated specialized fast (aCFXL) protocols. 18 As a result of this study, improvement was observed in biomechanical, topographic, and refractive characteristics following both procedures, and no statistical difference was found between the efficacies.…”
Section: Discussionmentioning
confidence: 65%
“…In a recent study, corneal cross-linking for progressive keratoconus was compared to ultraviolet A irradiation using the conventional Dresden or accelerated specialized fast (aCFXL) protocols. 18 As a result of this study, improvement was observed in biomechanical, topographic, and refractive characteristics following both procedures, and no statistical difference was found between the efficacies.…”
Section: Discussionmentioning
confidence: 65%
“…Ostacolo et al (2013) proved that VE-TPGS increased corneal penetration of riboflavin and corneal stiffness in transepithelial CXL on porcine corneas. They further confirmed the effectiveness of VE-TPGS to promote the permeation of riboflavin both in standard and accelerated CXL on KCN patients (Caruso et al, 2021). In a 24-month trial, VE-TPGS contributed to better clinical outcomes in transepithelial CXL with modified UVA irradiation (Caruso et al, 2016).…”
Section: Vitamin E-tocopherol Polyethylene Glycol 1000 Succinate (Ve-...mentioning
confidence: 59%
“…After sCXL and aCFXL, refractive, topographic, and biomechanical parameters all improved, showing the riboflavin-TPGS solution as a viable alternative as a permeation enhancer in CXL treatments. Riboflavin may provide further photo-protection by neutralizing ROS and UVA radiation produced by photo-induced activities, allowing it to penetrate deeper into the stroma [ 135 ].…”
Section: Randomized/clinical Prospects Of Tpgs and Its Patentsmentioning
confidence: 99%